Improvement of frozen semen quality of Garut Sheep through the addition of α-tocopherol into yolk egg-skim milk diluent - ., Herdis; ., Kusuma; Surachman, M; Sutama, I.K; Riza, M; Inounu, I; Purwantara, B; Arifiantini, I (Indonesian Animal Sciences Society, 2002)
The sperm is very fragile to lipid peroxide reaction, that it can easily broken during the process of freezing. To eliminate this consequences an antioxidant agent added into the extender. A research was done to observe the effect of antioxidant agent α-tocoferrol and butylated hydroxytoluene (BHT) presence in the extender on the quality of frozen semen. Once week, semen from six male Garut sheep ages about 2.5 years old was collected using artificial vagina and egg yolk skim-milk diluent used as the extender. The semen were treated in egg yolk skim-milk diluent without antioxidant as control, in egg yolk skim-milk diluent with α- tocoferrol 0,2 g/100 ml diluent and in egg yolk skim-milk diluent with butylated hydroxytoluene 0,2 g/100 ml diluent. The after thawing observation shown that in egg yolk skim-milk diluent with α- tocoferrol had life percentage (75.0 ± 3.5% vs 64.8 ± 7.8%) and membrane intact percentage (65.8 ± 6.8 % vs 55.2 ± 8.3%) significantly higher than control (P<0,05) but insignificantly different from with BHT addition. The presence of α-tocoferrol in the diluent, the motility percentage consideraly higher (P<0.05) than (45.8 ± 3.8%) using BHT addition (40.0 ± 4.5%) but not different from control (41.7 ± 4.1%); while acrosomal intake percentage after α-tocoferrol (54.8% ± 3.3%) expressively higher (p,0.05) than BHT addition (49.7 ± 3.6%) or control (49.8 ± 3.5%). In conclusion the presence of α-tocoferrol in the diluent could improve the quality of Garut sheep frozen semen. Key words: Antioxidant, sperm, Garut sheep